1946
DOI: 10.1021/ja01206a042
|View full text |Cite
|
Sign up to set email alerts
|

Allylic Rearrangements. XIX. Studies of the Ozonization of Allylic Systems1

Abstract: Ozonization of Allylic Systems 293 but are strongly dependent on degree of esterification, being highest for degree of esterification in the range 0.3 to 0.5. Enzyme-deesterified pectins form weaker ionic-bonded gels than do aciddeésterified pectins. Philadelphia, Pa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1951
1951
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…(CH3)3COCH2CH=CHCH2CH2CH=CHCH2OH As would be expected from a compound of this structure some formaldehyde is formed during ozonolysis (10). Furthermore, when the material is hydrogenated and then hydrolyzed one obtains some octanediol-1,8 as well as octanol-1.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…(CH3)3COCH2CH=CHCH2CH2CH=CHCH2OH As would be expected from a compound of this structure some formaldehyde is formed during ozonolysis (10). Furthermore, when the material is hydrogenated and then hydrolyzed one obtains some octanediol-1,8 as well as octanol-1.…”
Section: Methodsmentioning
confidence: 78%
“…Hydrogenation of (1,8-di-tert-butoxy-Ü,7-dimethyl-2, ß-ociadiene) fraction IV. Fraction IV (3.0 g., 10.65 mmoles) dissolved in absolute ethanol (60 ml.) was hydrogenated in the presence of Pt02 (50 mg.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zwitterionic fragment can also interact with a hydroxy group located in a different (not α) position with respect to the double bond, provided that its position is appropriate for such interaction [11]. Ozonolysis of octahydronaphthalene 36 in methylene chloride at -78°C, followed by treatment with copper(II) acetate and FeSO 4 , led to the formation of macrolide antibiotic 37 [12] (Scheme 13).…”
Section: Mementioning
confidence: 99%
“…Since conditions which might lead to overozonation were avoided, arabinose formation appeared to be an example of "abnormal ozonolysis" ofan allyliccompound, involving the rearrangement of an alkene-ozone reaction intermediate (2). In this connection Young et al (3) observed that allylic acetates were less prone to "abnormal ozonolysis" than their parent alcohols, while Milas and Nolan (4) claimed that some "abnormal ozonolyses" could be prevented by conducting ozonations in cold methanol. The mixture of l a and 2a, and their acetates (lb and 2b) were therefore ozonized under different conditions.…”
mentioning
confidence: 99%